2014
DOI: 10.1186/s40623-014-0158-y
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional magnetotelluric imaging of crustal fluids and seismicity around Naruko volcano, NE Japan

Abstract: We analyzed the 3-D resistivity structure beneath Naruko volcano, northeastern Japan, with the aim of imaging 3-D distribution of fluids in the crust for its volcanic and seismogenic implications. The data were recorded at 77 sites in total: 30 sites are new and are arranged in an approximately 5 × 5 km grid whereas the remaining older sites constitute two separate east-west profiles. We ran a 3-D inversion using full components of impedance tensors in the period range between 0.13 and 400 s. The resulting mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 36 publications
(46 reference statements)
3
56
0
Order By: Relevance
“…At greater depths, the LVZs beneath Naruko Volcano and Onikobe Caldera shift southwestward and southward, respectively. While the distinct LVZ beneath Onikobe Caldera has been recognized in previous studies (e.g., Nakajima and Hasegawa 2003;Okada et al 2014), the LVZ beneath Naruko Volcano had previously been resolved only by a magnetotelluric survey (Ogawa et al 2014). We also found a LVZ beneath Mt.…”
Section: Methodssupporting
confidence: 52%
“…At greater depths, the LVZs beneath Naruko Volcano and Onikobe Caldera shift southwestward and southward, respectively. While the distinct LVZ beneath Onikobe Caldera has been recognized in previous studies (e.g., Nakajima and Hasegawa 2003;Okada et al 2014), the LVZ beneath Naruko Volcano had previously been resolved only by a magnetotelluric survey (Ogawa et al 2014). We also found a LVZ beneath Mt.…”
Section: Methodssupporting
confidence: 52%
“…Based on a high-density, wideband magnetotelluric survey and 3D-imaging, Ogawa et al (2014) recently found a clear difference of resistivity at mid-crustal depth where a seismic survey detected possible fluid pools (Nakajima and Hasegawa, 2003;Ichiki et al, 2015;). Their study investigated the Naruko volcanic field in Northeast Japan which is representative of Quaternary volcanoes with a vast development of geothermal fields.…”
Section: The Reproduced Brine As a Swarm-related Fluidmentioning
confidence: 98%
“…Such complex tectonic settings suggest complex subsurface structures that may be related to the characteristic seismicity. Because electrical resistivity is sensitive to the presence of fluids, and subsequently the elasticity of the media, it is important to investigate how resistivity structures relate to earthquake generation Fujinawa et al 2002;Goto et al 2005;Guerer and Bayrak 2007;Wannamaker et al 2009;Yoshimura et al 2009;Ichihara et al 2011Ichihara et al , 2014Ichihara et al , 2016Ogawa et al 2014;Kaya et al 2013). To investigate the relationship between earthquakes and electrical resistivity structure, we gathered and analyzed the broadband (typically 0.003-10,000 s) magnetotelluric (MT) and telluric data, which resolve the resistivity structure from the surface to the depth of the upper mantle.…”
Section: Introductionmentioning
confidence: 99%